Ruang Lingkup Rekayasa Sipil 2020 di Indonesia - Mohammad Sahari Besari (Journal of Regional and City Planning, 1996)
At  the  end  of  the  Second  Long -Term  Development  Plan  (2020),  the  percentage  of  urban population  in  Indonesia  will  be  greater  than  rural  population.  This  phenomenon  will  put tremendous  pressure  on  the  provision  of  physical  infrastructure  to  the population. Physical infrastructure is strongly related to Civil Engineering. Entering the 21st century and beyond, the  development  of  civil  engineering  will  be  greatly  influence  by  Material  Science  and Computer Science.The increase of infrastrucure development in the next 25 years will also increase the need for Civil Engineering Human Resources. The quality and quantity of Civil Engineers in Indonesia are  still  relatively  low.  To  anticipate  the  need  of  infrastructure  development  in  The  Second Long-Term Development Plan, the quality and the output of Civil Engineering graduates need to be increased.